The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/mds.25801
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical correlates of caudate atrophy in Huntington's disease

Abstract: BACKGROUND The precise pathogenic mechanisms of Huntington disease (HD) are unknown, but can be tested in vivo using proton magnetic resonance spectroscopy (1H MRS) to measure neurochemical changes. OBJECTIVE To evaluate neurochemical differences in HD gene mutation-carriers (HGMC) vs. controls, and to investigate relationships among function, brain structure and neurochemistry in HD. Since previous 1H MRS studies have yielded varied conclusions about HD neurochemical changes, an additional goal was to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 46 publications
3
14
0
Order By: Relevance
“…The suggestion that relative metabolite concentrations may obviate partial volume effects, making it possible to sample, for example, caudate, without these concerns may represent oversimplification. Even where CSF constituents are measured relative to Cr, absent in CSF, this may falsely reduce metabolite estimations because spectroscopy averages voxel constituents.…”
Section: Discussionmentioning
confidence: 99%
“…The suggestion that relative metabolite concentrations may obviate partial volume effects, making it possible to sample, for example, caudate, without these concerns may represent oversimplification. Even where CSF constituents are measured relative to Cr, absent in CSF, this may falsely reduce metabolite estimations because spectroscopy averages voxel constituents.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, despite previous cross‐sectional studies indicating that caudate volume decrease mainly correlates with cognitive outcomes (Harris et al, ; Kim et al, ; Rosas et al, ), other studies have reported that it also correlates with the TFC status (Rosas et al, ; Tabrizi et al, ), suggesting its influence on functionality for daily living performance. In regard to the correlation with the UHDRS‐TMS decline, cross‐sectional studies have showed that the caudate volume decrease not only correlates with the global UHDRS‐TMS score (Coppen et al, ; Galvez et al, ; Padowski et al, ; Domínguez et al, , ), but also with specific domains of this scale, including chorea degree and eye movements’ deficits (Coppen et al, ; Galvez et al, ). Besides, longitudinal studies have shown that progressive caudate atrophy correlates with the UHDRS‐TMS performance at baseline (Domínguez et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest outcome measures for testing new therapies in future clinical trials and facilitate the calculation of sample sizes. The PREDICT HD study identified potential predictors of disease worsening, which allows for the selection of appropriate participants . Indeed, randomized, placebo‐controlled trials using these data have already been reported …”
Section: Natural History Studiesmentioning
confidence: 99%